Systems and methods for preparing and applying non-portland cement-based materials

Non-Portland cementitious materials, prepared by mixing blast furnace slag, geopolymer, and alkaline powder with sand, address corrosion and acid resistance issues in shotcrete, offering enhanced durability and strength.

JP7616965B2Active Publication Date: 2025-01-17ENTECH CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021131001
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-11
Publication Date
2025-01-17
Estimated Expiration
2036-11-04

AI Technical Summary

Technical Problem

Existing shotcrete materials, particularly those containing Portland cement and geopolymers, are susceptible to corrosion from organic materials and microbial-induced corrosion, and lack resistance to acids and high temperatures.

Method used

A method and system for preparing non-Portland cementitious materials by mixing blast furnace slag, geopolymer, alkaline powder, and sand, which are then conveyed and mixed with a liquid to form a partially liquefied material applied with compressed air, using a metering mixer, conduit, and nozzle.

Benefits of technology

The resulting materials exhibit high resistance to inorganic and organic acids, high initial strength, and increased durability, with improved resistance to high temperatures and thermal conductivity, forming a cohesive bond on vertical surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616965000005
    Figure 0007616965000005
  • Figure 0007616965000006
    Figure 0007616965000006
  • Figure 0007616965000007
    Figure 0007616965000007
Patent Text Reader

Abstract

To provide a method and system for preparing and applying a construction material.SOLUTION: A method for applying a construction material includes the steps of: mixing blast furnace slag material with geopolymer material to generate a non-Portland cement-based material; transporting the non-Portland cement-based material through a conduit to a nozzle; mixing the transported non-Portland cement-based material with a liquid at the nozzle to generate a partially liquefied non-Portland cement-based material; and applying the partially liquefied non-Portland cement-based material to a surface with compressed air.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE The present disclosure relates to construction materials, and more particularly to methods of preparing and applying construction materials. [Background technology]

[0002] Existing approaches in the field of sewer pipe repair and concrete repair and construction include the application of shotcrete, which can be projected by compressed air towards the surface that needs to be repaired or built. This shotcrete contains materials found in basic concrete, such as sand, Portland cement, and liquid. Depending on the site, this shotcrete can be in the form of either a dry mix application or a wet mix application. The term "dry mix" typically means that some or all of the dry materials are delivered by compressed air through a hose to a nozzle, where an operator can control the addition of liquid to the dry mix at the nozzle prior to the ejection of the material. On the other hand, the term "wet mix" typically means that premixed concrete, which includes liquid, is delivered through a hose and ejected.

[0003] Some companies have attempted to modify the material composition of shotcrete to obtain certain benefits. Thus, some approaches may include the use of geopolymers. However, these materials are often susceptible to corrosion as a result of the organic materials inherent in these products. For example, Milliken® manufactures a variety of products under its GeoSpray™ and GeoSpray™ AMS product lines. AMS products may be applied as a pre-treatment and / or post-treatment to GeoSpray™ products. GeoSpray is Portland cement-based with a negligible portion of geopolymer. This mixture is unstable to acids. AMS, by containing organic matter, combats the action of acids on Portland cement-based concrete as well as the action of microbially induced corrosion that occurs in Portland cement-based materials. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the problems of the prior art. [Means for solving the problem]

[0005] In a first embodiment, a method of applying a construction material is provided. The method may include mixing a blast furnace slag material, a geopolymer material, an alkali-based powder, and sand in a meter-mix device to generate a non-Portland cement-based material. The method may further include conveying the non-Portland cement-based material from the meter-mix device through a conduit to a nozzle, and mixing the conveyed non-Portland cement-based material with a liquid in the nozzle to generate a partially liquefied non-Portland cement-based material. The method may further include applying the partially liquefied non-Portland cement-based material to a surface with compressed air.

[0006] One or more of the following features may be included: In some embodiments, the geopolymer material is at least one of a volcanic rock flour or a pumice. The alkali-based powder may include a silicate. The mixing may be performed as a dry mix. The non-Portland cement-based material may be inorganic. The mixing may be performed in a mobile metered mix vehicle. The non-Portland cement-based material may include at least one of clay, gneiss, granite, rhyolite, andesite, picrite, potassium feldspar, albite, pumice, or zeolite. The mixing may include mixing with a portable gun, the portable gun configured to receive the non-Portland cement-based material from the metered mix device. Each component of the non-Portland cement-based material has a Blaine fineness value of approximately 2500 to 5000 cm. 2 / g.

[0007] In another embodiment, a system for applying a construction material is provided. The system may include a meter-mix device configured to meter and mix a blast furnace slag material, a geopolymer material, an alkali-based powder, and sand to generate a non-Portland cement-based material. The system may further include a conduit configured to convey the non-Portland cement-based material from the meter-mix device. The system may further include a nozzle configured to receive the non-Portland cement-based material and mix the conveyed non-Portland cement-based material with a liquid to generate a partially liquefied non-Portland cement-based material, the nozzle further configured to apply the partially liquefied non-Portland cement-based material to a surface with compressed air.

[0008] One or more of the following features may be included: In some embodiments, the geopolymer material may be at least one of a volcanic rock flour or a pumice. The alkali-based powder may include a silicate. The mixing may be performed as a dry mix. The non-Portland cement-based material may be inorganic. The mixing may be performed in a mobile metered mix vehicle. The non-Portland cement-based material may include at least one of clay, gneiss, granite, rhyolite, andesite, picrite, potassium feldspar, albite, pumice, or zeolite. The mixing may include mixing with a portable gun, the portable gun configured to receive the non-Portland cement-based material from the metered mix device. Each component of the non-Portland cement-based material has a Blaine fineness value of approximately 2500 to 5000 cm. 2 / g.

[0009] In another embodiment, a non-Portland cement-based construction material is provided. The non-Portland cement-based construction material may include a blast furnace slag material, a volcanic rock powder, an alkali-based powder, and sand. In some embodiments, the alkali-based powder may include a silicate.

[0010] The details of one or more implementations are set forth in the accompanying drawings and the description below. Other features and advantages will become apparent from the description, the drawings, and the claims.

[0011] Like reference numbers in the various drawings may indicate like elements. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a side view of a transfer system configured to meter, mix, and apply non-cementitious materials according to one embodiment of the present disclosure. [Diagram 2] FIG. 1 illustrates a rear side view of a transfer system configured to meter, mix, and apply non-cementitious materials according to one embodiment of the present disclosure. [Diagram 3] 1 is a flow chart illustrating operations involved in a non-cementitious coating process according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Embodiments of the present disclosure relate to construction materials having alkali-activated binders (i.e., non-Portland cement-based), and systems and methods for preparing and applying the construction materials. While many of the examples included herein are described in the context of concrete repair, it should be noted that the construction materials described herein can be used in any suitable application. Such applications include, but are not limited to, sewer repair projects, any concrete structure that is resistant to acid attack, and the like.

[0014] Referring to FIG. 1, a mobile meter-mix vehicle 100 is shown having a number of containers, compartments, and devices associated therewith. In some embodiments, the vehicle 100 may include a first container 102, which may be configured to store sand or other materials. A storage unit 104 may be configured to store water or other liquids. The vehicle 100 may further include a meter-mix device 106, which may include a number of components, including, but not limited to, a second container 108, an adjustable delivery mechanism 110, a portable gun 212, and the like. As shown in FIG. 2, the portable gun 212 may be connected to a nozzle 214 via a conduit or hose 216.

[0015] In some embodiments, the mobile meter-mix vehicle 100 may be configured to meter, mix, and apply a non-Portland cement based construction material. The metering and mixing of the material may occur on the vehicle (e.g., in the meter-mix device 106) or may occur prior to being placed in the second container 108. The material may be delivered to the nozzle 214 where it may be mixed with liquid from the storage unit 104 prior to being applied to the surface in need of construction or repair. Specifications for the non-Portland cement based construction material are described in more detail later in this specification.

[0016] In some embodiments, the non-Portland cement-based construction materials described herein can have higher strength values ​​than existing materials, can have high resistance and non-reactivity to inorganic and organic acids, and can have high early strength values. The non-Portland cement-based construction materials can have increased resistance to high temperatures and can have significantly increased strength and durability. In one example, the non-Portland cement-based construction materials can have excellent resistance to strong inorganic acids. Furthermore, products produced from the non-Portland cement-based construction materials can have excellent compressive strength and very low thermal conductivity. The materials for producing the non-Portland cement-based materials can be a dry mix (e.g., binder mix) of blast furnace slag material, geopolymer material, alkali-based powder, and sand in a metered mix device. In some embodiments, the binder mix can be used to produce the non-Portland cement-based materials.

[0017] In some embodiments, the binder mixture may include one or more of 4-45% by weight volcanic rock, 0-40% by weight latent hydraulic material, 10-45% by weight alkaline component selected from the group consisting of sodium silicate, alkali hydroxide, alkali carbonate, and mixtures thereof, and 20-90% by weight aggregate. In some embodiments, the binder mixture may include one or more of sulfate (SO4 2- ) may be included in the form of contaminants in a proportion of less than 1% by weight. In some embodiments, calcium may be included in the form of calcium oxide (CaO) in a proportion of at most 5% by weight of the binder mixture.

[0018] In some embodiments, the non-Portland cement-based construction material may include various types of geopolymeric materials. Geopolymeric materials may include, but are not limited to, volcanic rocks. Thus, the terms "geopolymeric material" and "volcanic rocks" may be used interchangeably within the scope of this disclosure. Such geopolymeric materials may include, but are not limited to, pozzolanic materials. Pozzolanic materials can react with strong alkalis, and the mixture is mixed with sand and / or gravel. Pozzolans (or pozzolanic materials) may be synthetic or natural rocks made from silicon dioxide, clay, limestone, iron oxide, and alkaline substances, and can be obtained by the action of heat. They can combine with calcium hydroxide and water to form bonds. Natural pozzolans may be magmatic rocks (e.g., volcanic tuffs, or German Rheintras), but may also be sedimentary rocks with a high percentage of soluble silicic acid, and in some cases, reactive aluminum oxide (clay). In some embodiments, pozzolans can be readily available raw materials and can be used as volcanic rock or geopolymer materials in non-Portland cement based construction materials. Natural materials such as volcanic rock or some other materials may also be used, but these may be more desirable when used in small proportions as fine powders (e.g., such volcanic rock powders).

[0019] In some embodiments, the non-Portland cement-based construction material may include any number of pozzolanic materials, including but not limited to finely ground clay, gneiss, granite, rhyolite, andesite, picrite, potassium feldspar, albite, pumice, zeolite, and the like, and mixtures thereof. These materials may be used in ground form and / or calcined and / or uncalcined. Additionally and / or alternatively, any raw material (including but not limited to ashes, pozzolans, slags) that contains sufficient amounts of reactive (e.g., metastable, glassy) SiO2 and Al2O3 may be suitable for embodiments of the present disclosure.

[0020] In some embodiments, the non-Portland cement-based construction material may include latent hydraulic materials. As used herein, the latent hydraulic materials may be, but are not limited to, fly ash, kaolin, truss, granulated slag (e.g., blast furnace slag materials), and / or mixtures thereof. In one example, fly ash in the form of lignite fly ash and anthracite fly ash may be used. In some embodiments, the pozzolanic material may be an activated silicate, such as slag sand or fly ash. In some embodiments, brick dust (calcined clay) or fly ash from plants that burn anthracite or lignite may be referred to as synthetic pozzolans. Thus, the term "fly ash" may refer to non-natural or synthetic pozzolans in this specification. In some embodiments, the particularly advantageous properties of fly ash may be caused by the advantageous ratio of silicon dioxide to aluminum oxide or calcium oxide, which allows these materials to be distinguished. However, as will be described in more detail below, the fly ash may contain portions of sulfates and / or calcium oxide, and therefore, if fly ash is used in the binder mix, a type of fly ash containing advantageous proportions of the specified materials may be used.

[0021] In some embodiments, the non-Portland cement-based construction material may include an alkali-based powder material and / or various mixed liquids. Some possible mixed liquids may include, but are not limited to, potassium and sodium water glasses, alkali hydroxides, etc. In some embodiments, the alkali, or alkali component, may be sodium silicate in the form of water-soluble sodium silicate, or in the form of sodium silicate powder. In some embodiments, spray-dried silicate may be used. When alkali hydroxides or alkali carbonates are used, they may be used in their respective liquid forms or as powders or granules.

[0022] In some embodiments, the SiO2 / Al2O3 containing component can be reacted with the alkaline liquid mixture to generate aluminosilicates with three-dimensional structures. These framework structures allow the formation of construction materials that do not require Portland cement in the molding compound.

[0023] As mentioned above, the binder mixture and / or each component of the binder mixture may contain calcium. In some embodiments, the binder mixture may contain calcium in the form of calcium oxide (CaO) moieties. These CaO moieties in the binder mixture and / or non-Portland cement-based construction materials may become calcium silicate hydrates after reacting with water-soluble alkali and / or other components, which may have known adverse chemical properties. Furthermore, calcium ions, which are a component of the cementitious crystalline structure, often exhibit undesirable availability, which may lead to a weakening of the cement structure over time. For this reason, the calcium moieties used may be as small as possible. The embodiments of the present disclosure that utilize SiO2 in the form of soluble silicic acid, iron oxide, Al2O3 in the form of aluminates, and calcium oxide may be practiced with water-soluble silicates or strong alkalis, resulting in an inorganic binder system with little or no calcium.

[0024] In some embodiments, at most 5% by weight of the binder mix may include calcium in the form of calcium oxide (CaO). In some embodiments, at most 2% by weight of the binder mix may include calcium in the form of calcium oxide. Additionally and / or alternatively, at most 1% by weight of the binder mix may include calcium in the form of calcium oxide.

[0025] In some embodiments, the binder mixture may contain sulfate (SO4 2-) may be present in the form of a pollutant and / or in a proportion of less than 1% by weight. Sulfates, in the form of their salts, are environmentally relevant substances. Increasing environmental pollution by sulfates is due to agricultural fertilization and waste management. Sulfates have been demonstrated to lead to soil and groundwater acidification. As sulfates are generally highly soluble in water, they are easily transported in groundwater, seepage, and surface water flows, which ultimately leads to increased acidification of the sulfate-containing spheres of material in waste storage facilities. Sulfates are reduced to sulfites through microbial action, which may have adverse effects on flora and fauna. In some embodiments, the sulfate portion of the binder mixture may be kept as low as possible to avoid at least these adverse effects. In some embodiments, the binder mixture may contain sulfate (SO4 2- ) may be present in the form of contaminants and / or in portions less than 0.5% by weight. In one embodiment, sulfates may be present in portions less than 0.25% by weight.

[0026] In some embodiments, the non-portland cementitious construction material may include sand. However, other aggregates may be used as well. For example, other aggregates used in the binder mix of non-cementitious concrete may include, but are not limited to, gravel, sand, basalt, etc. Other materials used in non-cementitious concrete may also be used without departing from the scope of the present disclosure. Additionally, perlite, expanded shale, pumice, or mixtures thereof may be used in various applications. In some embodiments, the binder mix may include 20-70% aggregate by weight. Additionally and / or alternatively, the binder mix may include 20-50% aggregate by weight. In one embodiment, 20-40% aggregate by weight may be included in the binder mix.

[0027] In some embodiments, the binder mixture may include water. Thus, in one embodiment, particularly high resistance to various chemicals (especially acids) can be demonstrated by a binder mixture consisting of 4-45 wt. % volcanic rock (e.g., geopolymer material), 0-40 wt. % latent hydraulic material (e.g., blast furnace slag material), 10-45 wt. % alkaline component (e.g., alkali), 20-90 wt. % aggregate (e.g., sand), and / or water. In some embodiments, the alkaline component may be sodium silicate, alkali hydroxide, and / or alkali carbonate. Additionally and / or alternatively, the binder mixture may contain sulfate (SO4 2- ) in the form of contaminants and / or in portions less than 1% by weight. In some embodiments, the binder mix may contain calcium in the form of calcium oxide (CaO) in portions of at most 5% by weight.

[0028] In operation, the components may be carefully metered and mixed (e.g., all or part of which may be done on the vehicle 100) and then delivered to the portable gun 212. The non-Portland cement based building material may be conveyed by compressed air through a conduit 216 to the nozzle 214. In one particular embodiment, potassium silicate, potassium silicate, 48% solids, 1.52 g / cm density. 3 , by weight SiO2:K2O 1.14, and some liquid may be added inside the nozzle 214 for a short period of time (e.g., less than 1 second) and thoroughly mixed, allowing the partially liquefied mixture to be applied to the surface of interest by compressed air.

[0029] The embodiments included herein may include mixtures that include some or all of the following: slag (e.g., non-natural pozzolana, base, or latent hydraulic material), fly ash (e.g., non-natural pozzolana and optional in the recipe), geopolymer (e.g., natural pozzolana and optionally ground volcanic material / rock), alkali / alkaline component (e.g., powder or liquid), other liquids (including water, optional), and sand / gravel or other aggregate. Examples of specific mixtures are provided below. However, the specific mixtures listed are provided by way of example only. Many additional and alternative embodiments are within the scope of this disclosure.

[0030] In one particular embodiment, the non-Portland cement based building material may be comprised of a mixture of the following: [Table 1]

[0031] In some embodiments, each component of the mixture has a Blaine fineness of about 2500 to 5000 cm 2 / g. The Blaine value is a standardized measure of the degree of fineness of cement. The Blaine value is the specific surface area (cm2) measured in a laboratory with a Blaine apparatus. 2 The Blaine value is given as 1 / g. For example, standard Portland cement (CEM I 32.5) has a Blaine value of 3,000 to 4,500. In some embodiments, the components of the binder mixture, volcanic rock, and / or latent hydraulic material may be used in a finely ground state with a Blaine value of greater than 3,000. In one embodiment, the volcanic rock and / or latent hydraulic material may have a Blaine value of greater than 3,500. Finely grinding the components can greatly increase the reaction rate. Finely grinding the volcanic rock can make it more workable and can also increase the resistance of the finished product to a wide range of chemicals, especially acids.

[0032] In another example, the non-Portland cement based building material may consist of a mixture of the following: [Table 2]

[0033] In another example, the non-Portland cement based building material may consist of a mixture of the following: [Table 3]

[0034] In some embodiments, the hydraulic binder may be replaced by a non-Portland cement-based construction material or binder mixture that is produced from the reaction of 4-45% by weight of volcanic rock, 0 (or more than 0)-40% by weight of latent hydraulic material, 10-45% by weight of an alkaline component, and 20-90% by weight of aggregate. In some embodiments, the alkaline component may be sodium silicate, an alkali hydroxide, and / or an alkali carbonate. Additionally, the binder mixture may contain sulfate (SO4 2- ) in the form of contaminants and / or in portions less than 1% by weight. In some embodiments, calcium may be included in portions of the binder mix of at most 5% by weight in the form of calcium oxide (CaO).

[0035] An embodiment of the non-Portland cement-based construction material produced unexpected results when the reaction time between the alkali component and the rock powder was sufficient to produce a cohesive molding material. After numerous tests, the molding material adhered very well to vertical surfaces, formed a tight bond, and had a compression strength value of 50 N / mm 2 (8000 psi) and was found to cure within 3 days.

[0036] In some embodiments, the binder mixture or non-Portland cement based construction materials may be used in a variety of technical applications, such as:

[0037] Dry mortar, plaster and sprayed concrete

[0038] By mixing dry components, dry mortar and plaster mixtures can be produced, in which case spray-dried reactive silicates or alkali hydroxides can be used, on which basis ready-made mixtures can be produced for use as spray concrete.

[0039] Foam concrete

[0040] Commercially available foamed concrete is a mineral-based, autoclaved and aerated mass construction material with a rough density of 300-800 kg / m 3 Foam concrete is usually made from raw materials such as lime, anhydrite, cement, water, and silica sand, and can combine structural support and thermal insulation properties. By using foam concrete in monolithic single-wall construction, it is possible to create highly insulated masonry structures.

[0041] In some embodiments, the manufacturing process may include finely grinding the silica sand (e.g., in a pebble mill) until the Blaine value exceeds 3,000. The components may be combined, for example, in a ratio of 1:1:4, with the addition of water to form a mortar mixture. In some embodiments, a trace of aluminum powder or paste may be added to the finished suspension. The mortar mixture may be poured into a water bath, where the aluminum metal granules form hydrogen gas in the alkaline mortar suspension. Air bubbles may be obtained, which foam the mortar, which gradually hardens. After 15 to 50 minutes, the end volume may be obtained. At this point, blocks may be obtained that are 3 to 8 meters long, 1 to 1.5 meters wide, and 50 to 80 centimeters high. These solid cakes or blocks may be cut into any desired size using wires. In some embodiments, these blocks may be cured in special steam pressure boilers (e.g. autoclaves) at temperatures of 180-200°C in an atmosphere of 10-12 bar of steam, where the material may reach its final properties after 6-12 hours. Foam concrete may be chemically approximately equivalent to the natural mineral tobermorite, but may be a synthetic material.

[0042] In addition to low thermal conductivity, the construction material may be characterized by non-flammability, which allows it to be rated, for example, A1 in the European fire protection classification. Modern foam concrete compositions may include a mixture of quicklime, cement, sand, and water. The composition can be characterized between lime-rich and cement-rich mixtures, depending on the oven-dry density and the ratio of quicklime to cement. Furthermore, sulfate carriers in the form of anhydrite or plaster may be used to improve the formation of a crystalline "house of cards" (unstable) structure in tobermorite, thereby enhancing the compressive strength and shrinkage properties. As a result of these discoveries, the addition of sulfate carriers in the form of anhydrite / plaster has been demonstrated to have manufacturing benefits over the past decade, and is therefore now a component of every foam concrete composition.

[0043] The construction material can obtain a fine pore structure by adding a small amount of aluminum powder during the mixing process. The finely dispersed aluminum in the mixture can react in an alkaline medium to generate hydrogen, which can slowly foam the raw mixture. This fine pore structure can remain in the product even after the actual hydrothermal curing process and can be substantially responsible for the properties of the final product.

[0044] In some embodiments, the manufacturing process may be divided into one or more of the following actions:

[0045] 1. Grind the silica sand and prepare the recycle slurry

[0046] 2. Mix and pour the foam concrete slurry

[0047] 3. Allow to expand, solidify and cut into rough cakes or blocks

[0048] 4. Hardening the uncut blocks under hydrothermal conditions

[0049] 5. Packing and storing the finished products

[0050] After mixing the foam concrete molding compound and pouring it into the steel moulds, a large number of complex chemical reactions can take place between the setting phase and the hydrothermal hardening phase. Hydration of quicklime can start if water is added during the mixing phase. As this is an exothermic reaction, the foam concrete molding compound warms up and can accelerate the hydration reaction of the cement phase. As a result, continuous hardening of the foam concrete molding compound can take place during the expansion caused by the evolution of hydrogen. In order to achieve a homogeneous pore structure, the gas evolution can be adjusted to the viscosity curve of the foam concrete molding compound, which expands. If this is not achieved, structural damage (so-called expansion cracks) can occur during the expansion, which cannot be corrected later during the production process. After a setting time of several hours, the uncut blocks can be cut into the appropriate rock layers with tensioned wires. The production process does not generate any waste, since all waste generated during the cutting process can be recycled in the composition.

[0051] Recyclability is the most important issue for the future. On the one hand, European requirements call for a reduction in waste, which is accompanied by increasing demands for the closure of waste landfills and for further recycling. On the other hand, increasing demands on environmental protection (e.g. minimum thresholds) and guidelines in the draft Alternative Building Materials Regulation in the comprehensive regulatory framework for groundwater / alternative building materials / soil conservation, which at least in some cases make the recycling of building materials available on the market more difficult. The leaching behavior with respect to sulfates can be caused by a sulfate concentration in the effluent of 900-1,650 mg / l. The threshold value for mineral-based alternative building materials is a sulfate concentration in the effluent of 250 mg / l according to the Alternative Building Materials Regulation. By omitting elemental sulfates and cement in the production of foam concrete, it is possible to significantly reduce the above-mentioned sulfate concentrations in the effluent, which may make it possible to use foam concrete construction waste as a mineral-based alternative building material.

[0052] In some embodiments, by using a non-cementitious binder according to the present disclosure, this disadvantage can be eliminated and, furthermore, the calcium content can be made very low, while other general technical properties can be unaffected.

[0053] Precast Concrete

[0054] Precast concrete parts, or precast concrete elements, are components made of concrete, reinforced concrete, or prestressed concrete that are prefabricated industrially in a factory and then placed in their final position, often by a crane. Precast concrete elements and precast reinforced concrete elements are versatile and are implemented in a variety of building techniques. In some embodiments of the present disclosure, precast elements for open canal construction may be manufactured.

[0055] fire protection

[0056] Plaster finishes for concrete elements and reinforced concrete elements are listed in DIN 4102 (fire reaction of building materials and elements). Plasters that are technically suitable for fire protection are insulating plasters of vermiculite and perlite as well as plasters according to DIN 18550, part 2.

[0057] In some embodiments, the spray mixture may be applied as a dry mortar, which is a mixture of mineral fibers such as glass wool, rock wool, or mineral wool, with a hydraulic binder, mixed with water immediately before application. The technical properties in terms of fire protection can be similar to those of sprayed asbestos.

[0058] The use of non-cementitious binders in the plaster finish can further increase fire resistance, since they may have more favorable expansion behavior and less shrinkage at high temperatures.

[0059] In some embodiments of the present disclosure, traditional mixers may not be used to produce the binder mixture. In some embodiments, a so-called kneader or continuous mixer is used to produce the premix, and an intensive or planetary mixer is used to mix in the aggregate, resulting in inorganic materials that can be forced or confined into a mold and produce the desired product after mechanical compression.

[0060] Table 4 below shows which mixing and application techniques may lead to which application areas for binder mixtures according to embodiments of the present disclosure. [Table 4]

[0061] In some embodiments of the present disclosure, a method for producing a moldable concrete molding material is provided. The method may include one or more of the following actions:

[0062] The method may include providing a binder mix that includes one or more of 4-45% by weight volcanic rock, 0-40% by weight latent hydraulic material, and 10-45% by weight alkaline component. In one example, the alkaline component or alkali may be selected from and / or include the group consisting of sodium silicate, alkali hydroxide, alkali carbonate, and mixtures thereof. In some embodiments, the binder mix may include sulfate (SO4 2- ) may be present in the form of contaminants in a fraction less than 1% by weight. Additionally, calcium may be present in the form of calcium oxide (CaO) in a fraction of at most 5% by weight of the binder mix. The method may further include the step of producing a premix of the binder mix using a kneader or continuous mixer. In some embodiments, the method may further include the step of mixing the premix with 20-90% by weight of aggregate using a central mixer or planetary mixer to produce a moldable concrete molding material. In some embodiments, this may be performed over a period of 1-5 minutes. In one embodiment, this may be performed over a period of about 2 minutes.

[0063] The method may further include compressing or vibrating the moldable concrete molding material to form pipes, precast concrete elements, sleepers, concrete blocks to form paving stones, sidewalk slabs, and the like.

[0064] In some embodiments of the present disclosure, a method for producing a moldable concrete molding material is provided. The method may include one or more of the following embodiments:

[0065] In some embodiments, the method may include providing a binder mix comprising one or more of 4-45% by weight volcanic rock, 0-40% by weight latent hydraulic material, and 10-45% by weight alkaline component. In some embodiments, the alkaline component may be selected from and / or include the group consisting of sodium silicate, alkali hydroxide, alkali carbonate, and mixtures thereof. In one example, the binder mix may include 20-90% by weight aggregate. In some embodiments, the binder mix may include sulfate (SO4 2- ) may be present in the form of contaminants in a proportion of less than 1% by weight. Additionally, calcium may be present in the form of calcium oxide (CaO) in a proportion of at most 5% by weight of the binder mix. The method may further include the step of producing a dry mix using a dry mixer. The method may further include the step of mixing the produced dry mix with water using a central mixer or a planetary mixer to produce a moldable concrete molding material.

[0066] In some embodiments of the present disclosure, a method for producing a sprayable concrete molding material is provided. The method may include one or more of the following embodiments:

[0067] In some embodiments, the method may include providing a binder mix comprising one or more of 4-45% by weight volcanic rock, 0-40% by weight latent hydraulic material, and 10-45% by weight alkaline component. In some embodiments, the alkaline component may be selected from and / or include the group consisting of sodium silicate, alkali hydroxide, alkali carbonate, and mixtures thereof. In some embodiments, the binder mix may include 20-90% by weight aggregate. In some embodiments, the binder mix may include sulfate (SO4 2-) may be present in the form of contaminants in a proportion of less than 1% by weight. Additionally, calcium may be present in the form of calcium oxide (CaO) in a proportion of at most 5% by weight of the binder mix. The method may further include the step of producing the dry mix using a dry mixer. In some embodiments, the method may further include the step of mixing the dry mix with water in a spray gun to produce a sprayable concrete forming material for immediate application.

[0068] In some embodiments, the binder mixture may be prepared for various application areas, including, for example, those listed above in Table 4. Examples 1-5 below may illustrate one or more embodiments of the present disclosure.

[0069] Example 1

[0070] In a mixer and kneader with an extrusion screw, 1 part finely ground volcanic rock (e.g., Blaine value 3,500), 0.15 parts fly ash, and 0.8 parts sodium silicate may be combined and vigorously mixed until a homogenous, pourable paste is obtained.

[0071] This paste may be mixed with 4 parts basalt and sand in a central mixer (or planetary mixer) for about 2 minutes. A soil moisture cement-free concrete is obtained, which is suitable for application as a surface concrete during the production of concrete blocks.

[0072] The sulfate content of this mixture may be 0.16% by weight and the calcium oxide content may be 0.8% by weight.

[0073] Compaction of such a mixture can be accomplished by compression and vibration, for example as performed in a block machine.

[0074] The resulting product may be characterized by significantly increased acid resistance, more favorable mechanical strength properties, and a significantly stronger color impression.

[0075] If other aggregate mixtures are used, such as gravel or sand, it is also possible to manufacture concrete pipes or special precast concrete elements, depending on the specific particle size distribution curve. By adjusting the moisture content and adapting the application technique (e.g. pouring, centrifugation, etc.), other product variations are possible.

[0076] Example 2

[0077] In an intensive mixer, 0.2 parts of granulated slag, 1 part of finely ground volcanic rock, and 3 parts of sand may be mixed. This dry mix may be placed in bags.

[0078] At the construction site, the 1 part mixture thus produced may be mixed with 0.7 parts sodium silicate to the desired consistency as a paving material mix.

[0079] The sulfate content of this mixture may be 0.19% by weight and the calcium oxide content may be 0.57% by weight.

[0080] The non-cementitious masonry and plastering mortars thus obtained can be applied to the surfaces to be coated in various ways (eg by conventional plastering, spraying, etc.).

[0081] Example 3

[0082] In a dry mixer, a dry mix may be produced consisting of 1 part volcanic pozzolan (e.g., Blaine value greater than 3,500), 0.4 parts fly ash, 1 part perlite, and 0.7 parts powdered sodium silicate.

[0083] This dry mix may be wetted with water by vigorous mixing at high shear, poured into a mold, and compressed.

[0084] The sulfate content of the wet mixture may be 0.32% by weight and the calcium oxide content may be 1.8% by weight.

[0085] In tests according to the above examples, samples were taken after the curing phase which showed no fractures or obvious cracks even after prolonged exposure to flame, no loss in mechanical strength properties after testing, and no damage whatsoever after exposure to freezing temperatures.

[0086] Example 4

[0087] In a dry mixer, a dry mix may be produced consisting of 1 part volcanic pozzolan (e.g., Blaine value greater than 3,500), 0.4 parts granulated slag, 1 part perlite, and 0.7 parts powdered sodium silicate.

[0088] This dry mix may be continuously fed to a spray gun and mixed with water to produce sprayable concrete. Corrosion of pipes and cables, sealing or coating of heat sensitive building materials and surfaces is easily possible by spray techniques with heat resistant and non-combustible non-cementitious molding compounds.

[0089] The sulfate content of this sprayable concrete may be 0.31% by weight and the calcium oxide content may be 1.29% by weight.

[0090] Example 5

[0091] For the production of foam concrete, 16.2 parts of volcanic rock, 3.35 parts of fly ash, and 23 parts of silica sand may be intensively premixed in a commercial mixer. This dry mix may be added to 33 parts of sodium silicate under high shear at 38°C and further mixed in the same mixer with 0.43 parts of aluminum paste.

[0092] The binder mixture may be poured into a Teflon mold and heated in the mold to 80°C for 120 minutes. The mixture may harden while strongly increasing in volume, but still be cuttable. For hardening, the mold may be placed in a hardening chamber where it may remain at 180°C for 30 minutes. Alternatively, an autoclave may be used at 120°C.

[0093] It is possible to obtain moldings with optical properties comparable to those of foam concrete obtained according to a typical method. Unlike typical foam concrete, this material may be acid-resistant, the sulfate content may be 0.21% by weight, and the calcium oxide content may be 0.6% by weight. In one embodiment, the resulting construction material may have a very low sulfate and calcium content.

[0094] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the disclosure. As used herein, the singular forms "a," "an," and "the" are intended to encompass the plural forms as well, unless the context clearly indicates the contrary. Furthermore, it is to be understood that the words "comprises" and / or "comprising," as used herein, specify the presence of stated features, integers, steps, operations, elements, and / or components, and do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof.

[0095] Corresponding structures, materials, acts, and equivalents of all means or step plus function elements in the following claims are intended to encompass all structures, materials, or acts that, in combination with other claimed elements, perform the function as specifically claimed. The description of the present disclosure has been presented for purposes of illustration and description, and is not intended to be exhaustive or to limit the present disclosure in the form disclosed. Various modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the present disclosure. The present embodiment has been selected and described in order to best explain the principles and practical applications of the present disclosure, and to enable others skilled in the art to understand the present disclosure in terms of various embodiments with various modifications suitable for the particular use envisaged.

[0096] Although the disclosure of the present application has been described in detail and by reference to embodiments thereof, it will be apparent that modifications and variations are possible without departing from the scope of the present disclosure as defined in the appended claims. [Appendix 1] 1. A method of applying a construction material, comprising: mixing the blast furnace slag material, the geopolymer material, an alkali, and sand in a meter mixer to generate a non-Portland cement based material; conveying the non-Portland cement based material from the meter-mix device through a conduit to a nozzle; mixing the conveyed non-Portland cement based material with a liquid at the nozzle to produce a partially liquefied non-Portland cement based material; applying the partially liquefied non-Portland cement-based material to a surface with compressed air; The method includes: [Appendix 2] 2. The method of claim 1, wherein the non-Portland cement based material comprises 4 to 45 weight percent geopolymer material. [Appendix 3] 3. The method of claim 2, wherein the non-Portland cement based material comprises 0 to greater than 40 wt. % blast furnace slag material. [Appendix 4] 4. The method of claim 3, wherein the non-Portland cement-based material contains 10 to 45 wt. % alkali. [Appendix 5] 5. The method of claim 4, wherein the non-Portland cement-based material comprises 20 to 90% by weight of sand. [Appendix 6] 6. The method of claim 5, wherein the non-Portland cement based material contains less than 1% by weight of sulfate. [Appendix 7] 7. The method of claim 6, wherein the non-Portland cement based material comprises at most 5% by weight of calcium oxide. [Appendix 8] 2. The method of claim 1, wherein the blast furnace slag comprises one or more of fly ash, kaolin, tassium slag, and granulated slag. [Appendix 9] 2. The method of claim 1, wherein the alkali comprises one or more of sodium silicate, alkali hydroxide, and alkali carbonate. [Appendix 10] 1. A system for applying a construction material, comprising: 1. A meter mix apparatus configured to mix a blast furnace slag material, a geopolymer material, an alkali-based powder, and sand to generate a non-Portland cement based material, the non-Portland cement based material comprising: 4 to 45 weight percent geopolymer material; 0 to 40% by weight of a blast furnace slag material; 10 to 45% by weight of an alkali; 20-90% by weight sand; less than 1% by weight of sulfate; At most 5% by weight of calcium oxide; The metering and mixing device includes one or more of: a conduit configured to convey the non-Portland cement based material from the meter-mix device; a nozzle configured to receive the non-Portland cement-based material and mix the conveyed non-Portland cement-based material with a liquid to generate a partially liquefied non-Portland cement-based material, the nozzle further configured to apply the partially liquefied non-Portland cement-based material to a surface with compressed air; A system including: [Appendix 11] 11. The system of claim 10, wherein the blast furnace slag comprises one or more of fly ash, kaolin, tassium slag, and granulated slag. [Appendix 12] 11. The system of claim 10, wherein the alkali comprises one or more of sodium silicate, alkali hydroxide, and alkali carbonate. [Appendix 13] 4-45% by weight of volcanic rock; 0 to more than 40% by weight of a latent hydraulic material; 10 to 45% by weight of an alkaline component; 20 to 90% by weight of aggregate; less than 1% by weight of sulfate; At most 5% by weight calcium; A binder mixture comprising: [Appendix 14] 14. The binder mixture of claim 13, wherein the alkaline component comprises one or more of sodium silicate, an alkali hydroxide, and an alkali carbonate. [Appendix 15] 15. The binder mixture of claim 14, wherein the alkaline component is sodium silicate. [Appendix 16] 16. The binder mixture of claim 15, wherein the sodium silicate is any one of water-soluble sodium silicate, powdered sodium silicate, and spray-dried silicate. [Appendix 17] 14. The binder mixture of claim 13, wherein the sulfate in the binder mixture is in the form of a contaminant. [Appendix 18] 14. The binder mixture of claim 13, wherein the sulfate in the binder mixture is less than 0.5 wt.%. [Appendix 19] 14. The binder mix of claim 13, wherein the calcium in the binder mix is ​​in the form of calcium oxide. [Appendix 20] 14. The binder mixture of claim 13, wherein the calcium in the binder mixture is at most 2% by weight. [Appendix 21] 14. The binder mixture of claim 13, wherein the volcanic rock is a pozzolan. [Appendix 22] 14. The binder mixture of claim 13, wherein the latent hydraulic material comprises one or more of lignite fly ash, anthracite fly ash, kaolin, and tulsa. [Appendix 23] 14. The binder mixture of claim 13, wherein the aggregate comprises one or more of gravel, sand, basalt, perlite, and expanded shale. [Appendix 24] 14. The binder mixture of claim 13, wherein the volcanic rock and / or the latent hydraulic material has a Blaine value of greater than 3,000. [Appendix 25] 14. The binder mixture according to claim 13, wherein the aggregate in the binder mixture is 20 to 70% by weight. [Appendix 26] 14. The binder mixture according to claim 13, wherein the aggregate in the binder mixture is 20 to 50% by weight. [Appendix 27] 14. The binder mixture according to claim 13, wherein the aggregate in the binder mixture is 20 to 40% by weight. [Appendix 28] 14. The binder mixture of claim 13, further comprising water. [Appendix 29] 1. A method for producing a sprayable concrete molding material, comprising: mixing one or more of 4-45% by weight of volcanic rock, 0-40% by weight or more of a latent hydraulic material, 10-45% by weight of an alkaline component, and 20-90% by weight of an aggregate in a dry mixer to produce a dry binder mix; mixing the dry binder mixture with water in a nozzle to produce a sprayable concrete forming material; The method includes: [Appendix 30] 30. The method of claim 29, wherein the dry binder mix contains less than 1% by weight of sulfate. [Appendix 31] 30. The method of claim 29, wherein the dry binder mix contains less than 5% by weight calcium. [Appendix 32] 1. A method for producing a moldable concrete molding material, comprising: mixing one or more of 4-45% by weight of volcanic rock, 0-40% by weight or more of a latent hydraulic material, 10-45% by weight of an alkaline component, and 20-90% by weight of an aggregate in a dry mixer to produce a dry binder mix; mixing the dry binder mixture with water using a planetary mixer to produce a moldable concrete molding material; The method includes:

Claims

1. A binder mixture comprising: 4-45% by weight of non-pumice volcanic rock flour, said non-pumice volcanic rock flour being a geopolymer material and having a Blaine value of greater than 3,000; greater than 0% by weight and not greater than 40% by weight of a latent hydraulic material, the latent hydraulic material comprising a pozzolan and having a Blaine value greater than 3,000; 10-45 wt. % of an alkaline component, the alkaline component comprising one or more of an alkali hydroxide and an alkali carbonate; 20 to 70% by weight of aggregate; less than 1% by weight of sulfate, the sulfate being in the form of a contaminant in the binder mix; 5% by weight or less of calcium; A binder mixture comprising:

2. 2. The binder mix of claim 1, wherein the sulfate in the binder mix is ​​0.5% by weight or less.

3. 10. The binder mix of claim 1 , wherein the calcium in the binder mix is ​​in the form of calcium oxide.

4. 2. The binder mix of claim 1, wherein the calcium in the binder mix is ​​less than or equal to 2% by weight.

5. 10. The binder mix of claim 1, wherein the aggregate comprises one or more of gravel, sand, basalt, perlite, and expanded shale.

6. 2. The binder mix of claim 1, wherein the aggregate in the binder mix is ​​20-50% by weight.

7. 2. The binder mix of claim 1, wherein the aggregate in the binder mix is ​​20-40% by weight.

8. The binder mixture of claim 1, further comprising water.

9. The binder mixture of claim 1, wherein the alkaline component comprises one or more of powdered sodium silicate and silicates.

10. The binder mixture of claim 1, wherein the latent hydraulic material comprises one or more of fly ash, kaolin, and tallow, and the fly ash comprises lignite fly ash and anthracite fly ash.

11. The binder mixture of claim 10, wherein at least one of the fly ash, the alkaline component, and the pozzolan are silicate sources for reaction of the binder mixture.

Citation Information

Patent Citations

  • Spraying mortar concrete composition

    JP1984030747A

  • Cement admixture and cement composition

    JP1998007443A

  • Hardenable inorganic composition

    JP1998025138A

  • Method of producing zeolite-containing hardened body

    JP2010280532A

  • Use of compounds containing aluminum oxide and silicon oxide for manufacturing hydrophilic building materials

    JP2013537163A